A new Dondice Marcus Er. 1958 (Gastropoda: Nudibranchia) from the Mediterranean Sea reveals interesting insights into the phylogenetic history of a group of Facelinidae taxa - Furfaro, Giulia; Mariottini, Paolo (Zootaxa, 2020)
The diversity of Mediterranean nudibranchs has yet to be thoroughly studied: new species are constantly described, and molecular approaches have revealed some cryptic species. A new facelinid species has been discovered based on specimens collected from the Tyrrhenian Sea (Mediterranean Sea). Integrative results of molecular analyses and of anatomical investigations support the description of Dondice trainitoi sp. nov. The characteristic chromatic body pattern and the black epithelium covering the masticatory jaws allow an unambiguous identification of the new taxon. Preliminary phylogenetic analyses based on multi-locus molecular markers (nuclear H3 gene and mitochondrial markers 16S rDNA and COI) surprisingly revealed paraphyly of the genus Dondice and the need of further studies including more taxa assigned to the currently accepted family Facelinidae. Furthermore, following an integrative taxonomy approach, considerations on the ecological behaviour characterizing most of the species involved in this study provide useful insights for understanding the evolutionary history of this facelinid group.